2019
DOI: 10.1002/cam4.2090
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of chromosome 17 abnormalities in patients with myelodysplastic syndrome treated with 5‐azacytidine: Results from the Hellenic 5‐azacytidine registry

Abstract: In patients with myelodysplastic syndrome (MDS), the prognostic significance of chromosome 17 abnormalities has not yet been fully elucidated, except for isochromosome 17q that has been characterized as an intermediate risk abnormality in the Revised International Prognostic Scoring System (IPSS‐R). To further characterize the prognostic significance of chromosome 17 abnormalities we analyzed the hematologic and prognostic characteristics of 548 adult patients with MDS treated with 5‐azacytidine through the He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Monosomy 17 predominantly appeared within the vCK population, but it had no effect on OS, which was different from the result in MK+ AML patients . This phenomenon was also found in the research by Diamantopoulos et al, which showed that although chromosome 17 abnormalities are often associated with poor prognosis, the results were confounded by the fact that abnormal 17 was also found in the CK context …”
Section: Discussionmentioning
confidence: 68%
“…Monosomy 17 predominantly appeared within the vCK population, but it had no effect on OS, which was different from the result in MK+ AML patients . This phenomenon was also found in the research by Diamantopoulos et al, which showed that although chromosome 17 abnormalities are often associated with poor prognosis, the results were confounded by the fact that abnormal 17 was also found in the CK context …”
Section: Discussionmentioning
confidence: 68%
“…The association between a poor prognosis and a chromosome 17 abnormality in patients has also been found in the context of a complex karyotype. This was also correlated with the loss of 17.13.1, which contains the genetic loci of the tumor suppressor gene p53 ( TP53 ) [ 65 ]. The significance of this cytogenetic aberration has been valuable in MDS and AML with TP53 mutations, due to its favorable response to hypomethylating agents (HMA), particularly decitabine [ 66 ].…”
Section: Cytogeneticsmentioning
confidence: 99%
“… 34 Myeloid neoplasms with isolated isochromosome 17q represent a distinct clinicopathologic entity with myelodysplastic and myeloproliferative features, high risk of leukemic transformation, and wild-type TP53. 34 The Hellenic 5-azacytidine registry 35 of 548 adult patients with MDS treated with 5-azacytidine reports 32 patients with a chromosome 17 abnormality (6 with i[17q], 15 with −17, 3 with add[17p] and the rest with other rarer abnormalities, mostly translocations). The presence of a chromosome 17 abnormality was associated with poor prognostic features (high IPSS, IPSS-R, and WPSS scores) and a low overall survival rate (15.7 vs. 36.4 months for patients without chromosome 17 abnormalities.…”
Section: Chromosome 17 Abnormalitiesmentioning
confidence: 99%